Analysing road accident triggers in Malaysia by using analytical hierarchy process / Norpah Mahat, Nurdiyana Jamil and Siti Sarah Raseli - Mahat, Norpah; Jamil, Nurdiyana; Raseli, Siti Sarah (Universiti Teknologi MARA Cawangan Pahang, 2020)
The number of road accident fatalities in Malaysia is increasing tremendously. One of the reasons of the road accident cases is the development of motorization sector. The problems of road accidents are extremely in critical state even though various preventive measures have been taken to reduce the rate of road accidents. Thus, this study will identify the actual factors and subfactors that contribute to the road accidents to make sure the preventive measures operate successfully. This study also will rank the factors and subfactors of road accidents based on the weight obtained. Therefore, a method called Analytical Hierarchy Process (AHP) was implemented to discover the triggers of road accidents in Malaysia. Questionnaires were given to three experts who have experience in dealing with road accidents. These experts were traffic police inspector, officer from road transport department and fire brigade officer. The pair-wise comparisons were rated by the experts according to Saaty scale from 1 to 9, scale 1 refers to Equal Important and scale 9 refers to Absolutely More Important. In order to obtain the result of each factor and sub-factor of the road accident, the average of comparison scales was determined before proceeding to other steps. In this study, the three main factors of road accidents involved are human behaviour, environment and vehicle. Among the factors of road accidents analysed, human behaviour which is the most affecting factor towards road accidents cases, followed by the environment and vehicle. Then, the first ranking of subfactors for each factor is drunk driving or driving under the influence, weather condition and brake failure are the main causes of the road accidents in Malaysia